Malária em gestantes no estado do Amazonas, Brasil - Pereira, Messias Zaguri (Brasil, 2024)
To evaluate the epidemiological profile of reported cases of malaria in pregnant women in the State of Amazonas – Brazil, between 2017 and 2021. Methods: This is a descriptive study. The target audience was made up of all pregnant women with a positive case of malaria and infection in the State of Amazonas. Data were collected from malaria notifications, in SIVEP – MALÁRIA of the Ministry of Health, for the period between January 1, 2017 and December 31, 2021. This study was submitted to the Research Ethics Committee (CEP) of the University Federal do Amazonas (UFAM), however, it was removed because it was a study with secondary data. Results: The study identified that there was a reduction in cases of malaria in pregnant women, with a predominance among those aged 20-29, of mixed race, with incomplete primary education, domestic occupation and in the 3rd trimester of pregnancy. Regarding the species, P. Vivax was responsible for the majority of infections. Conclusion: The study identified that malaria in pregnant women in Amazonas showed a drop in the number of reported cases, with the exception of 2021, which showed an increase in the number of cases. Therefore, the profile of these patients must be known to adopt prevention measures and adequate support, taking into account the location and seasonality of the disease.